1977
DOI: 10.1073/pnas.74.10.4582
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for an immunoglobulin-dependent antigen-specific helper T cell.

Abstract: Evidence from various systems suggests that thymus-derived lymphocytes can affect the quality of antibody responses by recognizing various portions of the immunoglobulin receptor of bone-marrow-derived thymus-independent lymphocytes. A model for this process is proposed involving two antigen-specific mature T helper cells, one of which also is specific for immunoglobulin determinants. These two cells act synergistically. Evidence from adoptive secondary antibody responses demonstrates that both cells are antig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
54
0

Year Published

1979
1979
1992
1992

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(60 citation statements)
references
References 17 publications
6
54
0
Order By: Relevance
“…Several studies have shown that the expression of germ-line idiotypes may be only dominant early in an antibody response (37,38). Furthermore, experiments using helper T cells from normal and anti-#-treated mice demonstrate that the Ig-dependent T cells were only active early during an anti-DNP response (9). Taken together, these data lend support to the concept that preferential activation of frequently represented B cells may be a result of the ThId cell set.…”
Section: Discussionsupporting
confidence: 69%
“…Several studies have shown that the expression of germ-line idiotypes may be only dominant early in an antibody response (37,38). Furthermore, experiments using helper T cells from normal and anti-#-treated mice demonstrate that the Ig-dependent T cells were only active early during an anti-DNP response (9). Taken together, these data lend support to the concept that preferential activation of frequently represented B cells may be a result of the ThId cell set.…”
Section: Discussionsupporting
confidence: 69%
“…Furthermore, adequate T-cell priming for a hapten does not require the presence of circulating antibody; this result argues against the existence of an Igdependent, antigen-specific helper T-cell population (16). Passively acquired antibody cannot function as the T-cell receptor in this system, because male Fx hybrids with the immune defect are unable to mount antibody responses to PC and lack detectable anti-PC antibodies in their serum (.5).…”
Section: Resultsmentioning
confidence: 95%
“…This may be due to the differential ability of B cells and other APCs to determine the class of CD4 T-cell response (41,42) and related to the difficulty in inducing "'anergy" in Th2-type T cells (43). Such selective T/B-cell interactions may also account for the extensive evidence produced in the past for the B-cell dependence of T-cell repertoires (44)(45)(46). In this view, self SAgs would play fundamental roles in regulating structural and functional T-lymphocyte repertoires, but the respective deletions, rather than constituting the bases of self tolerance, should instead be taken as a particular aspect ofrepertoire selection.…”
Section: Methodsmentioning
confidence: 96%